2012
DOI: 10.2527/jas.2011-4152
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of dried distillers grains with solubles to beef cows consuming low-quality forage during late gestation and early lactation1

Abstract: Three experiments were conducted to evaluate supplementation of dried distillers grains with solubles (DGS) to spring-calving beef cows (n = 120; 541 kg of initial BW; 5.1 initial BCS) consuming low-quality forage during late gestation and early lactation. Supplemental treatments included (DM basis) 1) 0.77 kg/d DGS (DGSL); 2) 1.54 kg/d DGS (DGSI); 3) 2.31 kg/d DGS (DGSH); 4) 1.54 kg/d of a blend of 49% wheat middlings and 51% cottonseed meal (POS); and 5) 0.23 kg/d of a cottonseed hull-based pellet (NEG). Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
5
18
1
Order By: Relevance
“…Increased MUN is an indication of excess dietary protein and/or decreased ruminal microbial synthesis. Increased MUN due to DDGS feeding in the present experiment, as well as other studies (Gunn et al, 2014;Winterholler et al, 2012), is likely caused by excess dietary protein, however elevated MUN could be a result of the decreased rumen degradable protein (RDP) content and/or the increased fat content of DDGS-based diets, as supplemental fat can have a negative effect on fiber digestion and can decrease microbial protein production (Coppock and Wilks, 1991). However, although formulated RDP content of the DDGS diet in the current study was lower compared with the CON diet, the RDP content of the DDGS diet still exceeded NRC (1996) recommendations.…”
Section: Milksupporting
confidence: 89%
See 4 more Smart Citations
“…Increased MUN is an indication of excess dietary protein and/or decreased ruminal microbial synthesis. Increased MUN due to DDGS feeding in the present experiment, as well as other studies (Gunn et al, 2014;Winterholler et al, 2012), is likely caused by excess dietary protein, however elevated MUN could be a result of the decreased rumen degradable protein (RDP) content and/or the increased fat content of DDGS-based diets, as supplemental fat can have a negative effect on fiber digestion and can decrease microbial protein production (Coppock and Wilks, 1991). However, although formulated RDP content of the DDGS diet in the current study was lower compared with the CON diet, the RDP content of the DDGS diet still exceeded NRC (1996) recommendations.…”
Section: Milksupporting
confidence: 89%
“…Cows fed DDGS had a greater percentage of milk fat on day 68 PP (P < 0.001), but not on day 116 PP (P = 0.34). Recent reports (Winterholler et al, 2012;Gunn et al, 2014) have indicated that milk fat in beef cows may be as low as 1.4% to 1.7%, however, it is possible that milk fat values in the present experiment were considerably lesser than expected because of incomplete emptying of the quarter at sampling. Nevertheless, it has been reported that within milking variation in milk components and fatty acids is low to none (Larsen et al, 2012;Rico et al, 2014).…”
Section: Milkcontrasting
confidence: 68%
See 3 more Smart Citations